Optimization of Residual Stresses in Laser-Mixed WC(Co,Ni) Coatings - Liu, C.W.; Jean, M.D.; Wang, Q.T.; Chen, B.S. (Проблемы прочности, 2019)
A ternary mixture of tungsten carbide (WC), cobalt (Co), and nickel (Ni) powders is prepared to form ceramic-metal composite coatings employed for laser cladding of 40Cr steel. This coating is investigated using the mixture design to evaluate the influence of its ratios on the residual stresses in the clads. The WC/Co/Ni ternary mixture exhibits higher residual stresses than those of the Co/Ni or WC/Ni binary mixtures, except for the WC/Co one. Single WC, Co, or Ni designs illustrate a high sensitivity of residual stresses, cracks pass through the interior of WC particles rather than around them, and the cracks mostly propagate along the eutectic phases at 50%Co–50%WC. A reduced special quartic model in the mixture design exhibits excellent fit, predicted and experimental values of residual stresses for these laser clads are in good agreement. Изготовлена трехкомпонентная смесь порошков карбида вольфрама (WC), кобальта (Со) и никеля (Ni) для получения металлокерамических композиционных покрытий, используемых для плакирования стали 40 Сr. При исследовании покрытия подбирался состав смеси для оценки влияния соотношения ее компонентов на остаточные напряжения в плакировках. Трехкомпонентная смесь WC/Co/Ni имеет более высокие остаточные напряжения, чем двухкомпонентные смеси Co/Ni или WC/Ni, за исключением WC/Co. Однокомпонентные составы WC, Co или Ni обусловливают высокую чувствительность остаточных напряжений, трещины скорее проходят внутри частиц WC, чем вокруг них, рост трещин происходит главным образом вдоль эвтектических фаз для состава 50%Co 50%WC. Приведенная специальная модель четвертого порядка показывает отличное соответствие при подборе состава смеси, хорошо согласуются между собой прогнозируемые и экспериментальные значения остаточных напряжений в лазерных плакировках. Виготовлена трихкомпонентна суміш порошків карбіду вольфраму (WC), кобальту (Со) і нікелю (Ni) для отримання металокерамічних композиційних покриттів, що використовуються для плакованої стали 40 Сг. При дослідженні покриття підбирався склад суміші для оцінки впливу співвідношення її компонентів на залишкові напруження в плакіровкі. Трикомпонентна суміш WC / Co / Ni має більш високі залишкові напруження, ніж двокомпонентні суміші Co / Ni або WC / Ni, за винятком WC / Co. Однокомпонентні склади WC, Co або Ni зумовлюють високу чутливість залишкових напружень, тріщини швидше проходять всередині частинок WC, ніж навколо них, зростання тріщин відбувається головним чином уздовж евтектичних фаз для складу 50% Co-50% WC. Наведена спеціальна модель четвертого порядку показує відмінне відповідність при підборі складу суміші, добре узгоджуються між собою прогнозовані і експериментальні значення залишкових напружень в лазерних плакіровках.